Ecotoxicologia da água residuária da suinocultura tendo minhocas como bioindicadoras - Paniago, Gustavo Gomes (2014)
The waste generated by the swine have high pollution potential, however, due to high organic 28 load, is presented as a good option in the fertilization of crops, nevertheless few is known about the 29 effects on soil fauna. The aim of this work was to study the environmental effects arising from the 30 use of swine wastewater using as bioindicators earthworms of the species Eisenia andrei through 31 the parameters of lethality, reproduction and escape. We studied the application of biodigester wastewater and manure storage tanks wastewater in four doses (0, 100, 200 and 300 m3 ha-132 ) in 33 three soils (Oxisol, Kandiudox and Artificial Tropical Soil). The experiments were conducted in the 34 period from 01/17/2014 to 06/07/2014. Data were analyzed using ANOVA one-way, Tukey test and 35 Pearson correlation matrices. No deaths occurred in the mortality test and there was no escape in 36 escape test. The reproduction test showed positive relationship between the amount of wastewater 37 applied and the number of hatched juveniles to most treatments. It is concluded that the application of biodigester wastewater and manure storage tanks wastewater to the dose of 300 m3 ha-1 38 does not 39 bring harm to earthworm populations in the three soils analyzed.